Liquefied natural gas (LNG), environment and the society (2012)
The environmental impact of the Liquefied Natural Gas (LNG) Company for the environment and social conditions using the Nigeria Liquefied Natural Gas (NLNG) in Rivers State, Niger Delta area of Nigeria as a case study is analysed in this paper. Specifically, the paper analyses the environment and social consequences of the operations of NLNG on the immediate environment. Data were collected from both the secondary and primary sources. The paper reveals that air borne diseases are the common ailments. Loss of potable water as well as farmland/wildlife is prevalent while societal values are shown to have broken down. However, NLNG has put some measures in place in order to mitigate some of these negative impacts of its operations on the environment.